SimConnect and SimTalk for distributed cyber-physical system simulation. (October 2013) - Pfeifer, Dylan; Valvano, Jonathan; Gerstlauer, Andreas
Real-time embedded and cyber-physical systems challenge simulation disciplines due to the heterogeneous tools used to model components in the system exploration and design phases. Termed "heterogeneity, " the mixed-model problem challenges multi-simulator coordination, where event causality must be preserved among simulators with different models of computation, signals, criteria for time advancement, and levels of abstraction. SimConnect and SimTalk enable heterogeneous, distributed, hardware/software co-simulation with a simplified backplane approach, emphasizing the simulation of software interacting with simulated world-model electrical, mechanical, and physical effects. The structure of SimConnect and SimTalk is described, adhering to the properties of a Kahn Process Network. Application of the tools to the coordination of three different simulators (TExaS, Ngspice, and Simulink) is presented to simulate closed-loop, hardware/software-based, Proportional-Integral-Derivative/Pulse-Width-Modulated control of a direct current motor. Results demonstrate agreement among simulator coordinations with configurable tradeoffs in speed versus accuracy.